AKTIVITAS INHIBISI ?-GLUKOSIDASE GRANULAR TEH HIJAU (Camellia sinensis) GRADE Arraca Yabukita HASIL DIAFILTRASI MENGGUNAKAN MEMBRAN NANOFILTRASI - Widiyarti, Galuh; Susilowati, Agustine; Aspiyanto, - (Teknologi Indonesia, 2012)
The activity of ?-glucosidase inhibition test of local granular green tea (Camellia sinensis) grade of Arraca Yabukita has been done. Granular green tea obtained by vacuum drying of the concentrate of the diafiltration process using nanofiltration membrane (DF-NF) at 50C for 0-80 hours. Every 8 hours of drying time, the analysis of water content, total polyphenols, and ?-glucosidase inhibitory activity of granular green tea were conducted. The?-glucosidase inhibitory activity test was performed by by Kim Yong-Mu method and compared to quercetin as standard. The results showed that, the drying process increases the ?-glucosidase inhibitory activity of granular green tea. At the optimum drying time 72 hours, the ?-glucosidase inhibitory activity of granular green tea is about 18 times higher than quercetin.